Impaired nutritional status in outpatients in remission or with active Crohn's disease – classified by objective endoscopic and imaging assessments. (October 2019) - de Castro, Marina Moreira; Corona, Ligiana Pires; Pascoal, Lívia Bitencourt; Rodrigues, Bruno Lima; de Lourdes Setsuko Ayrizono, Maria; Rodrigues Coy, Claudio Saddy; Leal, Raquel Franco; Milanski, Marciane
Summary: Background and aims: Crohn's disease is a chronic inflammatory disease consisting of alternated periods of relapse and remission. The disease is associated with altered body composition and micronutrient deficiencies. This study aimed to evaluate the nutritional status of Crohn's disease outpatients in remission and activity of the disease. Methods: Patients were classified according to Crohn's Disease Endoscopic Index of Severity or Magnetic Resonance Imaging scan. Anthropometric and biochemical analysis was performed for nutritional status evaluation. Results: A total of 60 patients were evaluated of which 31 were in endoscopic remission (mean Crohn's Disease Endoscopic Index of Severity: 1.76) and 29 in activity (mean Crohn's Disease Endoscopic Index of Severity: 7.88). Regarding markers of fat and lean mass, lower values were observed in the activity group when compared to the remission group ( p < 0.05). There was a positive correlation regarding the duration of the disease and the anthropometric parameters in patients with active disease. Interestingly, the prevalence of overweight/obese patients was 55% in remission group and 28% in activity group according to the Body Mass Index classification. In addition, lower levels of iron, folic acid and albumin were also observed in Crohn's disease activity group. Conclusions: We observed important differences in nutritional markers between patients in remission and activity phases, with higher prevalence of overweight/obese in patients with remission of the disease.